Psychological distress is related to poor health behaviours in COPD and non-COPD patients: Evidence from the CanCOLD study. (January 2019) - Paine, Nicola J.; Bacon, Simon L.; Bourbeau, Jean; Tan, Wan C.; Lavoie, Kim L.; Aaron, Shawn D.; Chapman, Kenneth R.; FitzGerald, J. Mark; Hernandez, Paul; Marciniuk, Darcy D.; Maltais, François; O'Donnell, Denis E.; et al.
Abstract: Background: Patients with psychiatric disorders (depression, anxiety) are more likely to have poor health behaviours, including higher smoking and lower physical activity (PA) levels. Smoking is a major risk factor for Chronic Obstructive Pulmonary Disease (COPD), and PA is critical for COPD management. However, no studies have assessed associations between psychological distress and these behaviours among patients with vs without COPD. This is a sub-analysis of the CanCOLD study that assessed the relationships between psychological disorders (depression, anxiety) and poor health behaviours (smoking, PA). Methods: 717 COPD and 797 matched non-COPD individuals from the CanCOLD study, completed the Hospital Anxiety Depression Scale (HADS) to assess anxiety and depression. Smoking behaviour was self-reported pack-years smoking. The CHAMPS PA questionnaire determined calorific expenditure as a PA measure. Regressions determined relationships between anxiety/depression and health behaviours, adjusting for age, sex, BMI, GOLD stage and COPD status. Results: Across the whole sample, we observed relationships between depression (β = 1.107 ± 0.197; 95%CI = 0.691–1.462; p < .001) and anxiety (β = 0.780 ± 0.170; 95%CI = 0.446–1.114; p < .001) and pack years. Higher depression (β = −0.220 ± 0.028; 95%CI = −0.275 to −0.165; p < .001) and anxiety (β = −0.091 ± 0.025; 95%CI = −0.139 to −0.043; p < .001) scores were related to lower PA. These associations were comparable across COPD and non-COPD patients. Conclusions: Results showed that higher levels of anxiety and depression were related to higher cumulative smoking and lower levels of PA in patients with and without COPD, suggesting symptoms of psychological distress is similarly associated with poorer health behaviours in COPD and non-COPD individuals. Future studies need to determine if treating symptoms of psychological distress can improve health behaviours and outcomes in this population. Highlights: This study showed significant relationships between depression and anxiety symptoms and smoking habits in patients with and at risk for COPD. This study also showed significant relationships between high levels of depression and anxiety symptoms and lower physical activity levels in these individuals. This cohort is extremely well characterized in terms of clinical detail, as well as being one of the largest cohorts of COPD patients. Clinicians should screen for depression & anxiety symptoms, in order to inform likelihood of uptake and maintenance of positive health behaviours.